Quality of olive oils and olive bagasse oil and their use in thermal processes (Research, Society and Development, 2021)
Olive oil is recognized due to its different properties, however, its most used form is in cold preparation, as there is still the belief that, once heated, olive oil would lose its beneficial properties to health and even form toxic substances. Thus, in order to assess the quality of olive oils and olive bagasse oil subjected to different temperatures and their use in thermal processes, the present study was developed at the Laboratory of Medicinal Plants, belonging to the State University's Department of Agronomy of Maringá. The following analyzes were performed when the oils reached temperatures of 10, 25 (room temperature), 140, 180, 220 and 260°C: acidity, peroxide index, iodine index and measurement of absorbance at 232 and 270 nm (ultraviolet). After the results obtained are compared with the standards of Codex Alimentarius, the Agência Nacional de Vigilância Sanitária, the Ministério da Agricultura, Pecuária e Abastecimento and the International Olive Council, it is concluded that even after heating, in most of the evaluated parameters, the oils remained in compliance with legislation, which can then be used in thermal processes.